Crystal structure and thermomechanical properties of CaO-PSZ ceramics synthesised from fused ZrO2. Issue 10 (July 2020) - Chen, Guo; Ling, Yeqing; Li, Qiannan; Zheng, Hewen; Li, Kangqiang; Jiang, Qi; Chen, Jin; Omran, Mamdouh; Gao, Lei
Abstract: Partially stabilised zirconia (PSZ) ceramics have attracted much interest because of their outstanding properties. In this study, fused ZrO2 was treated as a raw resource for the synthesis of CaO-PSZ ceramic materials through a facile sintering process. The crystal structure and thermomechanical properties of the synthesised CaO-PSZ ceramic samples were determined using XRD and SEM. The results revealed that various process parameters had different effects on the zirconia stability rate, including the temperature changing rate during the heating and cooling stages and the temperature and isothermal time during the quenching treatment; this was primarily a result of the thermodynamic characteristics of the martensitic conversion of ZrO2 ceramics. Secondly, the martensitic conversion process was revealed by XRD patterns, expressed as the partial conversion of c-ZrO2 to m-ZrO2 . Meanwhile, SEM-EDAX analysis highlighted the precipitation behaviour of the CaO stabiliser and the successful preparation of CaO-PSZ ceramics by sintering, represented by the gathering phenomenon of the acicular grains and particles, as the findings matched the stability rate analysis. This study can supply a sound reference for the synthesis of CaO-PSZ ceramics from fused ZrO2 .